The Right to a Public Trial and Closing the Courtroom to Disruptive Spectators - Stephen E. Smith (Washington University Law Review, 2015)
The Sixth Amendment to the United States Constitution provides, in part, that “[i]n all criminal prosecutions, the accused shall enjoy the right to a speedy and public trial.” Like many constitutional rights, however, the right to a public trial is not absolute. Courtrooms may be closed to the public in some situations. In Waller v. Georgia, the Supreme Court set forth the test trial courts should apply to determine whether a courtroom closure is appropriate. However, some courts, led by the Second Circuit’s per curiam decision in Cosentino v. Kelly, have declined to apply the Waller test to closures ordered for the purpose of excluding “disruptive” audience members in the courtroom. The exception of these “disruptive” courtroom closures from the Waller test is unnecessary and unsupported for several reasons. First, nothing in Waller or the Court’s subsequent right to a public trial case, Presley v. Georgia, indicates that the test applies in only limited circumstances. Second, cases declining to apply Waller’s test in these instances do not adequately explain why they believe the test has an exception at all. The Waller test properly balances Sixth Amendment values against the need for decorum and accounts for the serious nature of courtroom closures. Finally, the Waller test is easily administered by a trial court in effecting a courtroom closure, including those courtroom closures that exclude disruptive spectators. This anomaly in the rules governing courtroom closures should be eliminated.
Keywords: Waller v. Georgia; Cosentino v. Kelly; Sixth Amendment; Courtroom closure; Disruptive spectator; Right to public trial